From Exegesis to Performativity: An Epistemological-Phenomenological Study of the Transformation of Qur'anic Reception in Indonesia - Dwinuryudha Ken Rifqi; Andri Nirwana AN; Muthoifin (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study examines the paradigm shift in the reception of the Qur’an in Indonesia through epistemological and phenomenological perspectives, explaining its transformation from an object of interpretation into a subject of social performativity. Theoretical framework: The study integrates epistemology and phenomenology to analyze shifts in religious authority, meaning construction, and the lived experience of Qur’anic reception in Indonesian society. Literature review: Previous Living Qur’an studies mainly provide descriptive phenomenological accounts while overlooking epistemological dimensions. This study addresses that gap by linking reception practices with the transformation of religious knowledge. Method: A qualitative-philosophical approach is employed, combining epistemological inquiry and phenomenological analysis to interpret the transformation of Qur’anic reception. Results: The findings demonstrate three major transformations in the reception of the Qur’an in Indonesia. First, religious authority has shifted from textual interpretation toward subjective and communal experiences based on the perceived efficacy of Qur’anic practices. Second, phenomenologically, these practices reflect an internalization of meaning that extends beyond the linguistic content of the Qur’anic text. Third, these developments have produced a new "Epistemology of Reception," in which the Qur’an functions as an active social agent shaping religious and public life within Indonesian society. Implications: The study enriches Living Qur’an scholarship by offering an integrated framework for understanding the dynamic interaction between sacred texts and contemporary sociocultural contexts. Novelty: This study introduces the concept of "Epistemology of Reception," reconceptualizing the Qur’an as an active social force rather than merely an object of textual interpretation.